Female Labor Force Participation in Indonesia: The Role of Education, Wage, and Health - Susilawati, Sukma Ayu; Perwithosuci, Winny (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to examine the effect of the Female Head of Household (FHH), Provincial Minimum Wages (PMW), Involvement of Women in Parliament (IWP), Female Life Expectancy (FLE), Women's Mean Years School (EDUC) on Female Labor Force Participation in 34 provinces in Indonesia from 2020 to 2024.Methodology: This study utilized secondary data generated from BPS - Statistics Indonesia. Panel regression is employed to estimate the data. There are three approaches in panel data regression which are Common Effect (CE), Random Effect (RE), and Fixed Effect (FE). This study employed Chow and Hausman tests to choose the most appropriate model.Results: The Chow and Hausman test revealed that Fixed Effect Model (FE) is the most appropriate. Women's Mean Years of School negatively and significantly affected their labour force participation rate. Provincial Minimum Wages and Women's Involvement in Parliament had a positive and significant effect on the Female Labor Force Participation Rate. Meanwhile, neither the Female Head of Household nor Female Life Expectancy significantly influenced the Female Labor Force Participation Rate.Applications/Originality/Value: These findings have important implications for the formulation of gender-responsive, evidence-based employment policies to promote women's sustainable economic inclusion.